INTERPRETATION OF TRADITIONAL CHINESE CULTURAL SYMBOLS IN ZHANG YIMOU'S FILM SHADOW (2018) - Zuo Ke,; Mohd Erman Maharam, (Journal of Islamic, Social, Economics and Development, 2024)
This article examines the transmission and use of traditional Chinese cultural symbols through the lens of Zhang Yimou's 2018 film Shadow. This article discusses the meanings and characteristics of traditional Chinese cultural symbols, evaluates Zhang Yimou's film's cultural expression qualities, and investigates how he incorporates traditional Chinese cultural symbols into the film. Use textual analysis method to interpret traditional cultural symbols, including ink and wash painting, Qi and Seer ensemble, yin-yang and five elements, calligraphy, and architectural aesthetics. Finally, the communication effects of these traditional cultural markers in the film and their role in promoting Chinese culture are discussed. This study provides unique perspectives and ways for the transmission and development of Chinese culture, and it is a significant step in the promotion of Chinese films and culture.